METHODICAL PROBLEMS OF THE E-LEARNING OF PHYSICS BY THE MEANS OF INTERNET TECHNOLOGIES - A. Chaykovskiy; I. Korobova (Kherson State University, 2012)
The article describes the processes of the studying method's transformations and the role of the teacher in them; highlights the basic difficulties related with these changes and represented the technical and methodical means of overcoming them.